ANALISIS TREN DAN FAKTOR YANG MEMPENGARUHI PERTUMBUHAN DPK BANK HIMBARA: PENDEKATAN SLR - Handoko, Hendro; Zilal Hamzah, Muhammad; Tri Broto, Giri (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Third-Party Funds (TPF) represent the primary source of bank funding and determine banks’ capacity to perform their intermediation function. Within the State-Owned Banks Association (Himbara)—comprising BNI, BRI, Mandiri, and BTN—the growth of TPF during the 2015–2023 period exhibited significant fluctuations. These dynamics were influenced by various factors, including macroeconomic conditions, digital transformation, internal bank performance, and regional socio-economic characteristics. Previous studies indicate that external variables such as exchange rates and the Loan to Deposit Ratio (LDR) affect TPF growth, with LDR tending to have a negative short-term impact. Meanwhile, digital transformation in banking has reshaped customer behavior and expanded financial service access, although its successful implementation requires policy harmonization to maintain stability and public trust. This study employs a Systematic Literature Review (SLR) approach to identify, evaluate, and synthesize empirical findings related to the determinants of TPF growth, focusing on its components: demand deposits, savings deposits, and time deposits. The results reveal that TPF growth in Himbara banks is simultaneously influenced by macroeconomic indicators, digital banking development, capital strength, operational efficiency, and regional socio-economic conditions. This study contributes both theoretically and practically by providing a comprehensive overview of strategic factors affecting fund mobilization in Himbara banks and serves as a basis for formulating adaptive and sustainable funding strategies in the digital era.